Repeat HER2 Testing in Synchronous Axillary Metastases: Necessary or Overkill?. (21st September 2018) - Clarke-Brodber, Anna-Lee; Rahn, Heidi; Mohammad, Sahir; Pesce, Catherine; Sullivan, Megan
Abstract: Objectives: HER2-positive breast cancers are often treated with neoadjuvant chemotherapy (NAC), especially with known axillary lymph node (LN) involvement. The rate of pathologic complete response (pCR) for these tumors is high (30.4%-72.4%) and therefore oncologists do not want to miss any patient who may benefit from targeted NAC, resulting in requests to repeat HER2 immunohistochemistry (IHC) on core biopsies from synchronous positive axillary LNs. Past literature has demonstrated changes in HER2 status from the primary tumor to metastatic disease, often with intervening treatment. We used tissue from patients with HER2-negative breast cancers and nodal involvement at presentation to determine if there was any difference in HER2 status. Methods: The pathology database was searched for all female invasive breast cancer patients with HER2-negative primaries and synchronous axillary macrometastasis (>0.2 cm) diagnosed between January 2010 and June 2016. Both hormone receptor (HR)–positive and triple-negative (TN) tumors were included. Pertinent clinical data were retrieved from the medical record and patients who received NAC were excluded. Slides and blocks were available for 238 patients. Tissue microarrays (TMAs) were made using two 0.1-cm cores from both the primary tumor and axillary metastasis. HER2 IHC (Ventana antibody 4B5) was performed on the TMAs. Results: Tissue from both the primary and metastatic cores remained for evaluation on the HER2 IHC slides for 220 patients. All (HR and TN) remained HER2 negative on retesting. None of the patients had different HER2 results in the primary vs metastatic tumor. Conclusion: When controlled for prior NAC, HER2 IHC results between HER2-negative primary invasive breast tumors and synchronous positive axillary LNs are 100% concordant. The additional LN testing provided no added benefit, and changes in practice patterns in this situation should be considered. A single-institution cost analysis demonstrated savings of 27, 089.16.